2013
DOI: 10.1111/hepr.12254
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic oxidative stress in ovariectomized transgenic mice expressing the hepatitis C virus polyprotein is augmented through suppression of adenosine monophosphate‐activated protein kinase/proliferator‐activated receptor gamma co‐activator 1 alpha signaling

Abstract: Our study demonstrated that hepatic oxidative stress was augmented in OVX transgenic mice expressing the HCV polyprotein by attenuation of antioxidant potential through inhibition of AMPK/PGC-1α signaling. These results may account in part for the mechanisms by which HCV-infected women are at high risk for HCC development when some period has passed after menopause.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 38 publications
(71 reference statements)
0
3
0
Order By: Relevance
“…overcome the detrimental oxidative stress associated with ovariectomy by decreasing the levels of hepatic MDA and increasing the levels of the hepatic total glutathione. Menopause can induce abnormal serum lipid production, substantially affecting liver function, causing excessive production of reactive oxygen species (ROS), starting lipid peroxidation, impairing liver function, and adversely affecting the cardiovascular system [2,8,29]. Hepatocyte possesses an enzyme system to protect against oxidative stress, and regulating endogenous antioxidants in the liver not only prevents fatty liver production but also prevents the onset of cardiovascular disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…overcome the detrimental oxidative stress associated with ovariectomy by decreasing the levels of hepatic MDA and increasing the levels of the hepatic total glutathione. Menopause can induce abnormal serum lipid production, substantially affecting liver function, causing excessive production of reactive oxygen species (ROS), starting lipid peroxidation, impairing liver function, and adversely affecting the cardiovascular system [2,8,29]. Hepatocyte possesses an enzyme system to protect against oxidative stress, and regulating endogenous antioxidants in the liver not only prevents fatty liver production but also prevents the onset of cardiovascular disease.…”
Section: Discussionmentioning
confidence: 99%
“…For studies related to postmenopausal women, natural menopausal animal models and artificially ovariectomized models are used. Among them, ovariectomized models are more commonly used [ 28 , 29 ]. Several studies have also shown that estrogen receptor alpha (ER α ) is associated with weight control and lipid accumulation [ 7 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…There are several markers for evaluating oxidative stress, including 8-hydroxyguanosine, 4-hydroxynonenal protein, and activity of glutathione and superoxide dismutase (35,36). Additionally, the levels of d-ROM and BAP have been used to evaluate oxidative status.…”
Section: Discussionmentioning
confidence: 99%